Equality-based arguments for the decriminalization of abortion in Brazil: towards new legal opportunities - Cunha de Barros Penteado, Taís Sofia (Revista de Investigações Constitucionais, 2020)
This article aims to contribute to the abortion debate in Brazil, by looking deeply at how the equality principle is being mobilized by pro-decriminalization actors in the specific context of ADPF 442, the lawsuit in which the constitutionality of the abortion restriction up to the 12th week is challenged before the Brazilian Supreme Court. We map and classify the different formulations of equality arguments presented by the claimant and other relevant actors. We then discuss one of the formulations – the formulation that characterizes abortion as a means of group subordination - in light of the legal opportunity structure available in Brazil. We argue that while this argument faces a challenge posed by the narrow formulations of the equality principle in general in Brazil, it also opens up a new window for arguing, for being close in formulation to an important equality case ruled by the Supreme Court – ADPF 186, an affirmative action case.